Tuning higher order electric field resonances in plasmonic hexagonal arrays by oxygen-plasma treatment - Nonthanan Sitpathom (2022)
Experimental and simulation studies show that a hexagonal array of polystyrene particles on a gold substrate, capped with gold semi-shells, results in increased optical confinement of the resonance modes in comparison with those for arrays without metallic substrate or capping. Well-ordered arrays of polystyrene beads were fabricated by convective deposition, a solution-based self-assembly process. The polystyrene particles exhibited strong optical concentration, with photonic and plasmonic modes as detected in optical spectra and modelling. The resonance wavelengths of the plasmonic hexagonal array were modified by treating the hexagonal arrays with oxygen plasma at fixed power of 150 W for time periods of 0–10 min. The plasma treatment reduced the vertical height of the polystyrene particles, and the resonances were tuned and sharpened after plasma treatment. This increase is attributed to the improved uniformity of the gold semi-shell coating distributed over the polystyrene particles. Additionally, the plasma treatment increased the refractive index of the polystyrene particles due to cross-linking. Devices with these plasmonic hexagonal arrays enable enhanced light–matter interactions, with the flexibility to post-tune the resonance wavelengths.